Internalisasi Pendidikan Qurani Dalam Pembelajaran Pendidikan Kewarganegaraan Untuk Membentuk Karakter Religius Warga Negara Di Era Digital - Widodo, Bali; Nugraha, Yogi (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2023)
Deviant behavior that is contrary to religious teachings and Pancasila values as a result of recent technological and information developments often occurs both in the family and community environment. Education as an effort to humanize humans into civilized humans is again a concern. This study aims to determine the concept of internalization of Quranic Education in learning Civic Education in shaping civic civilization. This research uses the library research method, namely by collecting data through scientific articles or sources related to the research topic. The analysis of this discussion explains that Quranic Education is a value education derived from Islam that teaches about humans with noble morals. Internalization of Quranic Education in Civic Education learning can develop students' mentality and spirituality into individuals with religious character.